Resiliensi lansia yang tinggal sendiri dalam menghadapi COVID-19 - Ananda Saadatul Maulidia; Eko April Ariyanto; Sahat Saragih (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
COVID-19 has infected almost all countries in the world. So our government asks people to stay at home and practice physical distancing. This is certainly not easy, especially the elderly. The elderly who live alone certainly have greater challenges in dealing with COVID-19. Therefore, the need for self-capacity is called resilience. The purpose of this study is to find out how resilience is carried out by the elderly who live alone in the face of COVID-19. This study used qualitative research methods. Informants in this study amounted to 3 people with an age range of 60 years and over. Data collection techniques were carried out by in-depth interviews using cell phones. The results of the study show that resilient behavior makes the elderly who live alone can view the problem of this pandemic positively. The informants felt that the presence of COVID-19 did not make them anxious for themselves, because they believed that the occurrence of COVID-19 was indeed God's will (emotional regulation). In addition, they are optimistic that this COVID-19 will soon pass (optimism). With the Covid-19, some activities that are usually carried out have indeed changed, but the informants carried out other alternative activities to overcome their boredom and loneliness, such as gardening (creativity). In addition, the existence of a policy at home makes informants more focused on achieving their worship (achievement).